2017
DOI: 10.1063/1.4999644
|View full text |Cite
|
Sign up to set email alerts
|

Observation of distorted Maxwell-Boltzmann distribution of epithermal ions in LHD

Abstract: A distorted Maxwell-Boltzmann distribution of epithermal ions is observed associated with the collapse of energetic ions triggered by the tongue shaped deformation. The tongue shaped deformation is characterized by the plasma displacement localized in the toroidal, poloidal, and radial directions at the non-rational magnetic flux surface in toroidal plasma. Moment analysis of the ion velocity distribution measured with charge exchange spectroscopy is studied in order to investigate the impact of tongue event o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Anisotropy in ion velocity distribution can be caused by fusion-born energetic ions or fast magnetohydrodynamic events (e.g. rapid 'tongue'-shaped deformation of flux surfaces reported in the Large Helical Device (LHD) [16]) or fast ions produced by charge exchange with NBI particles [17]. Furthermore, recent 1D3V particle-in-cell (PIC) simulation showed that the high concentrations of energetic particles can intensify the harmonic ICE [18], suggesting that the intensification in high-harmonic ICE described in Figure 3(c) and Figure 3(d) can be interpreted as the increase of fast ions at the outer edge region near the pedestal collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropy in ion velocity distribution can be caused by fusion-born energetic ions or fast magnetohydrodynamic events (e.g. rapid 'tongue'-shaped deformation of flux surfaces reported in the Large Helical Device (LHD) [16]) or fast ions produced by charge exchange with NBI particles [17]. Furthermore, recent 1D3V particle-in-cell (PIC) simulation showed that the high concentrations of energetic particles can intensify the harmonic ICE [18], suggesting that the intensification in high-harmonic ICE described in Figure 3(c) and Figure 3(d) can be interpreted as the increase of fast ions at the outer edge region near the pedestal collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Submillisecond bursts of ICE driven by marginally super-Alfvénic NBI deuterons in NSTX-U were observed [75] to be spatially colocated with internal transport barriers that are well within (by tens of centimetres) the plasma. The redistribution of the initially helically-trapped ions that are implicated in burst kinetic MHD [16,17,19] or abrupt tongue deformation [21,22] could generate a distinct, transient, highly non-Maxwellian distribution in velocity space, perhaps involving the expelled ions and freshly trapped ions. Let us therefore make the assumption (for this, or some as-yet-unknown, reason) that a transient, spatially localised, highly non-Maxwellian population of 3.02MeV fusion-born protons could be responsible for the ICE spectral peaks b, c and d in Fig.…”
Section: Observations Of Bursting Ice From Lhd Deuterium Plasmamentioning
confidence: 99%
“…However, it has been seen that the spatial potential distribution inside the plasma can be highly system specific as it depends on various other experimental conditions, like external magnetic field [12], the discharge source [13], and the type of gases used [14]. Numerous examples can be found in the literature, which shows significant deviation from the theoretical prediction of plasma potential with regard to the experiments [12,13,15,16,17]. Particularly, the magnetized plasma systems is one such example where the presence of external electrodes in contact with the plasma body are found to dramatically alter the equilibrium properties of plasma from the Boltzmann to a non-Boltzmann potential distribution profile, particularly across magnetic fields [12,13,17].…”
Section: Introductionmentioning
confidence: 99%